Evaluation of oral health-related quality of life and its association with mental health status of patients with type 2 diabetes mellitus in the post-COVID-19 pandemic era: A study from Central Saudi Arabia - Thirunavukkarasu, Ashokkumar; Alharbi, Majed Sonitan; Salahuddin, Mohammad; Al-Hazmi, Ahmad Homoud; ALruwaili, Bashayer Farhan; Alsaidan, Aseel Awad; Almutairi, Ahmad Saeed; Almuhaydib, Rayyanah Nasser; Alrashoudi, Latifah Ibrahim (Frontiers in Public Health, 2023)
Background and objectives The association between oral and mental health is reciprocal, in which poor oral health may lead to several mental health issues, especially among patients with diabetes. The present study evaluated oral health-related quality of life (OHRQOL) and its association with mental health conditions among patients with type 2 diabetes mellitus (T2DM) in central Saudi Arabia. Methods: The Arabic version of the Oral Health Impact Profile-14 (OHIP-14) questionnaire and the Depression, Anxiety, and Stress Scale-21 Items (DASS-21) were used to assess the OHRQOL and mental health status of patients with diabetes. We utilized logistic regression analysis to identify the predictors of poor OHRQOL, and Spearman’s correlation test to identify any correlations between OHIP-14 and overall DASS-21 scores, as well as each subscale. Results: Of the 677 patients included in the present study, 52.7% had a poor OHRQOL, which was significantly higher (positive association) among patients with a longer duration of diabetes (adjusted odds ratio [AOR] = 3.31; 95% confidence interval [CI] = 1.96–4.17) and those who did not periodically monitor their oral health (AOR = 2.85; 95% CI = 1.76–3.89). Some forms (mild, moderate, severe, or extremely severe) of depression, anxiety, and stress were observed in 59.7, 71.1, and 67.1% of the participants, respectively. Furthermore, we found that the total OHRQOL scores had a significant positive association with depression (AOR = 2.32, 95% CI = 1.34 – 3.71, p = 0.001), anxiety (AOR = 1.81, 95% CI = 1.22 – 2.79, p = 0.003), and stress (AOR= 1.43, 95% CI = 1.14 – 2.19, p = 0.026). Conclusion: The results of the present study suggest the importance of appropriate and targeted health education programs for T2DM patients to ensure periodic dental examinations and oral health. Additionally, we recommend counseling sessions for all T2DM patients with trained healthcare providers to improve their mental health status during follow-up visits at outpatient diabetes care centers.